The power of alignment: how personalized information shapes voter decisions - Ioannidis, Nikandros (My University, 2025)
This study examines the effects of personalized political information on voter-party congruence and electoral behavior through an online survey experiment embedded in a Voting Advice Application (VAA) during the 2021 parliamentary elections in Cyprus. Drawing on Downs’ paradox, it hypothesizes that personalized affinity information would increase electoral participation and proximity voting by lowering informational costs. The experiment, involving approximately 4% of the Cypriot electorate, finds that such information significantly increases the likelihood of participation – by up to 10 percentage points – and encourages broader party consideration beyond single-party allegiance. However, no evidence is found that it shifts vote intentions toward more ideologically congruent parties. Despite increased awareness, voting choices remain largely stable, suggesting that short VAA interactions may activate participation without altering entrenched preferences. These findings underscore the value of VAAs as tools for engagement, even if their capacity to reshape vote choice is limited.
Keywords: Voting advice applications (VAAs); electoral engagement; voter-party congruence; personalised information